2013
DOI: 10.5897/ingoj12.021
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge assessment on the effects of climate change due to keeping livestock in urban and peri-urban areas of Dar es Salaam, Tanzania

Abstract: This paper discusses assessment results of the respondents who kept livestock in urban and periurban areas in the three municipalities of Kinondoni, Ilala, and Temeke in Dar es Salaam city region, if they had knowledge that their activities had an effect on climate change. Data show that over two thirds of the respondents did not think that the presence of solid waste, liquid waste, and pollution resulting from keeping livestock would have an effect on climate risks in the future. However, the respondents thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Rainfall is segmented into long rains and short rains. The long rains start from mid of March to the end of May while short rains start from mid October to late December (Mlozi et al, 2013). Nonetheless, there are empirical evidences revealing the decline in rainfall in both seasons in the whole of Dar es Salaam Region where the study area is found (START, 2011).…”
Section: The Study Areamentioning
confidence: 98%
See 4 more Smart Citations
“…Rainfall is segmented into long rains and short rains. The long rains start from mid of March to the end of May while short rains start from mid October to late December (Mlozi et al, 2013). Nonetheless, there are empirical evidences revealing the decline in rainfall in both seasons in the whole of Dar es Salaam Region where the study area is found (START, 2011).…”
Section: The Study Areamentioning
confidence: 98%
“…Despite that, PUF is affected by the incidences of the rising temperature, decreasing the amount of rainfall and the prevalence of droughts (Shretha and Sada, 2013). Urban farming particularly livestock sector is also vulnerable from the decrease in rain cycles especially in Dar es Salaam Region (Mlozi et al, 2013). Agricultural production in urban and peri-urban areas depends on cheap water and cheap energy for nitrogen based fertilizers and agricultural processes all of which contribute to climate change (Havaligi, 2009).…”
Section: Peri-urban Farming and Climate Changementioning
confidence: 99%
See 3 more Smart Citations